Yes1 signaling mediates the resistance to Trastuzumab/Lap atinib in breast cancer. - Tatsuaki Takeda; Hiromasa Yamamoto; Hirotaka Kanzaki; Ken Suzawa; Takahiro Yoshioka; Shuta Tomida; Xiaojiang Cui; Ramachandran Murali; Kei Namba; Hiroki Sato; Hidejiro Torigoe; Mototsugu Watanabe; et al. (PLoS ONE)
Background Overexpression of human epidermal growth factor receptor 2 (HER2) is observed in approximately 15-23% of breast cancers and these cancers are classified as HER2-positive breast cancer. Trastuzumab is the first-line targeted therapeutic drug for HER2-positive breast cancer and has improved patient overall survival. However, acquired resistance to trastuzumab is still a critical issue in breast cancer treatment. We previously established a trastuzumab-resistant breast cancer cell line (named as BT-474-R) from a trastuzumab-sensitive HER2-amplified cell line BT-474. Lapatinib is also a molecular-targeted drug for HER2-positive breast cancer, which acquired the resistance to trastuzumab. Acquired resistance to lapatinib is also an issue to be conquered. Methods We established trastuzumab/lapatinib-dual resistant cell line (named as BT-474-RL2) by additionally treating BT-474-R with lapatinib. We analyzed the mechanisms of resistance to trastuzumab and lapatinib. Besides, we analyzed the effect of the detected resistance mechanism in HER2-positive breast cancer patients. Results Proto-oncogene tyrosine-protein kinase Yes1, which is one of the Src family members, was amplified, overexpressed and activated in BT-474-R and BT-474-RL2. Silencing of Yes1 by siRNA induced both BT-474-R and BT-474-RL2 to restore the sensitivity to trastuzumab and lapatinib. Pharmaceutical inhibition of Yes1 by the Src inhibitor dasatinib was also effective to restore the sensitivity to trastuzumab and lapatinib in the two resistant cell lines. Combination treatment with dasatinib and trastuzumab induced down-regulation of signaling molecules such as HER2 and Akt. Moreover, the combination treatments induced G1-phase cell-cycle arrest and apoptosis. Consistent with cell line data, high expression of Yes1 mRNA was correlated with worse prognosis in patients with HER2-positive breast cancer. Conclusion Yes1 plays an important role in acquired resistance to trastuzumab and lapatinib in HER2-positive breast cancer. Our data suggest that pharmacological inhibition of Yes1 may be an effective strategy to overcome resistance to trastuzumab and lapatinib.